An aberrant variant of Histoplasma capsulatum var. capsulatum. - Sutton, D A (1997)
We studied an aberrant culture of Histoplasma capsulatum var. capsulatum isolated from synovial fluid collected from the right elbow of a patient from Kansas. Colonies on Sabouraud glucose agar and other routine mycological media were glabrous to soft, moist, heaped, deeply folded or convoluted, and orange-brown with a white, irregular margin. Microscopically, hyphae were hyaline, septate, and branched and remained totally devoid of conidiation over a period of 2 years on all mycological media. Conversion to the yeast form was achieved on Pine's medium at 37 degrees C. Colonies at early stages of growth were smooth, moist, pasty, shiny, and orange-brown but soon became wrinkled and slightly raised and produced oval, thin-walled cells measuring 2 to 3 by to 4.5 microns which multiplied by polar budding. The identity of the isolate was further confirmed by utilizing the Accuprobe DNA and the exoantigen test for H. capsulatum var. capsulatum.